The Role of Formulaic Expressions through Lesson Study in Improving Writing Skills of Islamic Elementary Students in Indonesian Language Subject - Fawaid, Achmad; Malika, Huzaimah Sindu (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2025)
This study investigates the role of formulaic expressions in enhancing the writing skills of Islamic elementary students through the lesson study framework. It is due to the fact that many students in Islamic Elementary School (Madrasah Ibtidaiyah) deal with some challenges in developing writing fluency, coherence, and grammatical accuracy. This study aims to explore how formulaic expressions, combined with the iterative cycles of lesson study, can improve these skills. The method of this study uses classroom observations, interviews with teachers and students, and assessments of students' writing performance across two lesson study cycles. This study resulted a significant increase in student engagement, fluency, and overall writing competence due to the structured integration of formulaic expressions with lesson study. This study also highlights the effectiveness of using formulaic language to reduce cognitive load and enhance linguistic scaffolding in writing tasks. It also implies that this approach can be applied to various educational settings to support writing development in young learners.